CLUSTER’S LIFE CYCLE: HOW SPECIFIC PUBLIC POLICIES CAN CHANGE THE TREND - Antonelli, Gilda; Moschera, Luigi; Mollona, Edoardo (European Scientific Journal, ESJ, 2014)
The aim of this paper is to contribute to the discussion on clusters competitiveness and paths dependence. Italian clusters offer a recognized example of territorial production model, however, recent studies in the field showed that it is passing through a crisis. Several enterprises are delocalizing their manufacturing processes abroad losing the shared knowledge that characterizes the cluster culture. This paper is part of the area of studies that analyses cluster dynamics (Krackhardt, 1994; Ahuja, 2000; Hansen, 2002; Zaho & Aram, 1995; Nooteboom, 1992, 2004; Gulati and Gargiulo, 1999) and explores the inter-organisational relationship in a cluster situated in the Campania region and concentrated, in particular, in the urban area of Naples. The focus of the empirical analysis is on the companies in the railway industry. The cluster has two central actors: an institution and a company linked to other companies in the cluster as their main final client. In the first stage we analysed the strategic motivations that stimulate these actors to intervene and support processes of increasing the level of inter-organisational collaboration between the companies in the cluster. The first stage of the analysis that we present below is based upon structural indicators peculiar to the network analysis methodology. These first results over a short period allow us to highlight several limitations of the analysis of the main structural indicators of a network. However, the qualitative analysis is a useful complement to understanding the strategic behaviour of actors that operate in a very cohesive cluster, conditioning the evolution of the life cycles of the cluster and inter-organisational relationships between its actors.